Microstructure, Nano-, and Macro-Indentation Characterization of AISI 302 Steel After High-Temperatures Aging - Omar Ben Lenda; Hajar El Ganich; El Madani Saad (East European Journal of Physics, 2023)
The structural and mechanical studies of the AISI 302 steel aim to design a correct heat treatment in order to optimize its mechanical properties. In this study, we investigated the influence of temperature and time of aging on the structural and mechanical characteristics of the AISI 302 steel. The steel was aged at temperatures of 1100°C and 1200°C and for times ranging from 0 to 6000 minutes. The structural and mechanical characterization techniques used were the metallurgical microscope, nanoindentation technique, and macro-hardness test. At the microstructural level, an increase in the time or temperature of the aging contributed to an increase in the austenite grains size of AISI 302 steel. This microstructural change led to a decrease in the nanohardness and a drop in the macro-hardness between the unaged and aged conditions of AISI 302 steel.